THE ABSENCE OF FORGIVENESS AND ITS PSYCHOLOGICAL CAUSES - Vieira Gois dos Santos, Thais (Revista Gênero e Interdisciplinaridade, 2024)
Forgiveness transcends cultures, religions, and belief systems, yet many struggle with the idea and practice of forgiveness. This article delves into the absence of forgiveness in its various nuances, exploring the psychological complexities underlying this difficulty. We investigate deep-rooted causes that may hinder one’s ability to forgive, from emotional traumas to ingrained thought patterns. Additionally, we examine how theological understanding, particularly rooted in biblical wisdom and theological knowledge, can contribute to the forgiveness process. Forgiveness is not merely an isolated act; it is a multifaceted process involving introspection, empathy, and often a fundamental shift in how we perceive ourselves and others. By unraveling the layers of forgiveness and its psychological implications, we hope to offer a comprehensive insight into this crucial theme, providing tools and perspectives to aid those struggling with forgiveness in their journey towards healing and personal growth.